Twin studies research in genes, teeth and faces - Pinkerton, Sandra K.; Rogers, James R. (James Robert) 1941-; Bockmann, Michelle R.; Hughes, Toby E.; University of Adelaide.|bSchool of Dentistry (Adelaide, South Australia University of Adelaide Press, 2015)
"This book is about an ongoing long-term research initiative led by researchers from the School of Dentistry at the University of Adelaide. The aim of this book is to provide an overview of the studies of the teeth and faces of Australian twins and their families that have extended over more than thirty years."--Back cover.
Colour illustrations on endpapers.
Includes bibliographical references.
Also free available online. Address as at 19/09/2016:|uhttps://www.adelaide.edu.au/press/titles/twin-studies/twin-studies-ebook.pdf
Keywords: Twins -- Research -- Australia; Dentistry -- Research -- Australia; Genetics -- Research -- Australia; Face -- Research -- Australia; Medical genetics -- ustralia; Australian